2021
DOI: 10.5500/wjt.v11.i7.290
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation in lung transplantation: Indications, techniques and results

Abstract: The use of extracorporeal membrane oxygenation (ECMO) in the field of lung transplantation has rapidly expanded over the past 30 years. It has become an important tool in an increasing number of specialized centers as a bridge to transplantation and in the intra-operative and/or post-operative setting. ECMO is an extremely versatile tool in the field of lung transplantation as it can be used and adapted in different configurations with several potential cannulation sites according to the specific need of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 59 publications
1
30
0
1
Order By: Relevance
“…Extracorporeal membrane oxygenation is an extremely versatile tool in the field of LTx as it can serve as a BTT before transplantation, as a support modality during transplantation, and as a rescue strategy after transplantation (3,(6)(7)(8). The data presented here confirmed the essential role of ECMO in LTx, especially the prominent contribution in the intra-and post-operative periods.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Extracorporeal membrane oxygenation is an extremely versatile tool in the field of LTx as it can serve as a BTT before transplantation, as a support modality during transplantation, and as a rescue strategy after transplantation (3,(6)(7)(8). The data presented here confirmed the essential role of ECMO in LTx, especially the prominent contribution in the intra-and post-operative periods.…”
Section: Discussionsupporting
confidence: 70%
“…Extracorporeal membrane oxygenation (ECMO) is used with increasing frequency in LTx to provide prolonged cardiac and respiratory support (5)(6)(7)(8). After careful patient selection and the involvement of a multidisciplinary team, several single-and multi-center studies have reported successful use of ECMO as a bridge to transplantation (BTT) (9)(10)(11)(12) as well as a postoperative rescue strategy for primary graft dysfunction (PGD) (13), which has prompted intraoperative use of ECMO during LTx (7).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a central ECMO must be surgically removed and complicates mobilisation in the ICU. These drawbacks can be avoided by inserting a VVA ECMO or connecting the arterial cannula to the subclavian artery using a prothesis [ 3 , 5 , 7 ].…”
Section: Strategymentioning
confidence: 99%
“…A major change in intraoperative management was the use of extracorporeal membrane oxygenation (ECMO) as a closed system as compared to the cardiopulmonary bypass (CPB). With different cannulation strategies (veno-arterial and veno-venous (VA ECMO and VV ECMO), as well as central and peripheral cannulation), it became possible to support both oxygenation and, if needed, circulation with minimal anticoagulation and with reduced invasiveness [ 7 ]. Regarding the application of this procedure, different strategies exist depending on the respective transplant centre.…”
Section: Introductionmentioning
confidence: 99%
“…This is guided by haemodynamic status and graft function. A new ECMO circuit can also be initiated in the post-operative period to manage haemodynamic instability, primary graft dysfunction or reperfusion injury (64). Patients requiring VA-ECMO support into the post-operative period have a higher mortality rate when comparted to VV-ECMO (2).…”
Section: Lung Transplantationmentioning
confidence: 99%